Physiological and Performance Impacts After Field Supramaximal High-Intensity Interval Training With Different Work-Recovery Duration - Brandão, Leandro Henrique Albuquerque; Chagas, Thaysa Passos Nery; Vasconcelos, Alan Bruno Silva; de Oliveira, Vivian Conceição; Fortes, Leonardo de Sousa; de Almeida, Marcos Bezerra; Mendes Netto, Raquel Simões; Del-Vecchio, Fabrício Boscolo; Neto, Ezequias Pereira; Chaves, Leury Max Silva; Jimenez-Pavón, David; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2020)
Due to great possibilities of handling the external load, the high intensity interval trainings (HIIT) could present different performances and physiological responses and even more so when these protocols are applied over ground. The present study aimed to evaluate the, performances, metabolic responses, and CK and LDH activities produced through two supra-maximum HIIT protocols in recreational endurance runners. Fifteen recreational male runners performed two HIIT protocols in randomized order with multiple conditions: 1) H15 (n=15) with a HIIT protocol of 15:15 work-recovery duration, and 2) H30 (n=15) with a HIIT protocol of 30:30 work-recovery duration. Both protocols were performed in similar intensity (130% vV̇O2max) and with one set until voluntary exhaustion. Blood samples were collected and estimated the levels and activities of blood lactate (BLac: mmol. L-1), glucose (GLU: mg. dL-1), creatine kinase (CK: U/L) and lactate dehydrogenase (LDH: U/L). BLac and GLU were collected at pre, five and ten moments after the H15 and H30 protocols were performed. Blood collections used to measure the activities of CK and LDH enzymes were verified in the pre, 24 and 48 h after the protocols. Distance traveled (m), total time (s), and bouts performed (rep) were also registered. Significant differences between conditions H15 and H30 were observed in the bouts performed (p=0.001; ES=1.19). Several statistical differences were found over time for BLac [pre vs. post5’ (both conditions: p=0.001), pre vs. post10’ (both conditions: p=0.001), and post5’ vs. post10’ (H30: p=0.004)], CK [pre vs. post24 (H15: p<0.001; ES=0.97 and H30: p=0.001; ES=0.74) post 24 vs post48 (H30: p=0.03; ES=0.56)], and LDH [pre vs. post24 (H15: p=0.008; ES=1.07 and H30: p=0.022; ES=0.85). No statistical differences between conditions were observed for any blood parameter. In conclusion, both protocols generated similar performance and physiological responses, however, H30 showed a significant reduction in lactate and CK activities after 10 min and 48 h, respectively.